Improvement of sylvite flotation from halite by starvation feeding the collector octadecylamine. Issue 43 (3rd July 2018) - Li, Shoujiang; Xu, Bo; Chen, Peng; Zhao, Yunliang; Nie, Guihua; Song, Shaoxian
Abstract : The flotation rate of halite increased much faster than that of sylvite on increasing the ODA dosage. Sylvite locked with halite which allowed the halite to float upward along with the sylvite. Starvation feeding the collector improved the separation of sylvite from halite. Abstract : In order to improve the separation of sylvite and halite in SDIC Xinjiang Lop Nur potash Co. Ltd. (SLNP), in this work, the flotation kinetics of sylvite and halite under different collector dosages were investigated. It was observed that the increased speed of halite was much faster than sylvite in terms of flotation rate with an increase in octadecylamine hydrochloride (ODA) dosage. The reason for the upward floating of halite explored by SEM-EDS was that sylvite was locked with halite, thus it can float up along with sylvite. According to the analysis results, a strategy of starvation feeding the collector was employed to increase the flotation rate difference between sylvite and halite, and consequently improve the separation of sylvite and halite. It has been demonstrated that starvation feeding the collector is an efficient method for obtaining high grade sylvite, because it can not only improve the separation of sylvite and halite but also decrease the consumption of ODA in the flotation process.